2014
DOI: 10.1016/j.celrep.2014.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Luminal Cells Are Favored as the Cell of Origin for Prostate Cancer

Abstract: The identification of cell types of origin for cancer has important implications for tumor stratification and personalized treatment. For prostate cancer, the cell of origin has been intensively studied, but it has remained unclear whether basal or luminal epithelial cells, or both, represent cells of origin under physiological conditions in vivo. Here, we use a novel lineage-tracing strategy to assess the cell of origin in a diverse range of mouse models, including Nkx3.1+/–; Pten+/–, Pten+/–, Hi-Myc, and TRA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
111
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(121 citation statements)
references
References 37 publications
(62 reference statements)
8
111
1
1
Order By: Relevance
“…Hi basal cell 1,000 21 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) Intriguingly, human basal-and luminal-derived tumors demonstrate histologically distinct phenotypes when challenged with the same oncogenes, MYC and AKT1. Tumors derived from basal cells are of a higher grade than tumors derived from luminal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Hi basal cell 1,000 21 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) Intriguingly, human basal-and luminal-derived tumors demonstrate histologically distinct phenotypes when challenged with the same oncogenes, MYC and AKT1. Tumors derived from basal cells are of a higher grade than tumors derived from luminal cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that by loss of tumor suppressor genes, both P-bSCs and P-lSCs can give rise to prostate cancer (12,13). Therefore, understanding how to manipulate the two populations of P-SCs to either remain silent in a dormant state or undergo terminal differentiation should provide new avenues to retrain prostate cancer progression and relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Luminal cells are generally accepted as the cells of origin for human PC 26,29 and human pathologists diagnose the disease based on the absence of basal cell markers. 42 Evidence from the mouse implicates both luminal cells 18,39,41 and basal cells 22,25,38 39 Alternatively, neoplastic transformation may commence in differentiated progenitor cells (intermediate cells) that co-opt self-renewal programs form tissue stem cells. 5 Finally, even mature differentiated postmitotic prostatic luminal cells could be reprogrammed by oncogenic pressure into tumor-initiating cells.…”
Section: Discussionmentioning
confidence: 99%